2005
DOI: 10.1001/archinte.165.11.1280
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Antipsychotic Drug Prescribing in Nursing Homes

Abstract: This study detected the highest level of antipsychotic use in NHs in over a decade. Most atypicals were prescribed outside the prescribing guidelines and for doses and indications without strong clinical evidence. Failure to detect positive relationships between behavioral symptoms and antipsychotic therapy raises questions about the appropriateness of prescribing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
150
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(160 citation statements)
references
References 25 publications
6
150
1
3
Order By: Relevance
“…Contrary to expectations, two out of three patients on antipsychotics in the present study were prescribed conventional drugs. Jn most of the previous studies outside Europe, the ratio of atypical to conventional antipsychotic use is 3:2 or 2: 1 (8,9,35,36), although these reports came from studies on elderly residents in long-term institutional care. Variations between countries in the ratio of atypical to typical antipsychotic use may be due to the different costs and national reimbursement policies as well as to prescription rules and procedures.…”
Section: Aging Elinmentioning
confidence: 99%
“…Contrary to expectations, two out of three patients on antipsychotics in the present study were prescribed conventional drugs. Jn most of the previous studies outside Europe, the ratio of atypical to conventional antipsychotic use is 3:2 or 2: 1 (8,9,35,36), although these reports came from studies on elderly residents in long-term institutional care. Variations between countries in the ratio of atypical to typical antipsychotic use may be due to the different costs and national reimbursement policies as well as to prescription rules and procedures.…”
Section: Aging Elinmentioning
confidence: 99%
“…1 In nursing homes, psychotropic agents are given to up to twothirds of dementia patients. [2][3][4][5] The safety of antipsychotic medications in older adults has been called into question. The United States Food and Drug Administration and Health Canada have issued advisories stating that certain atypical antipsychotics (risperidone, olanzapine and aripiprazole) have been associated with an increased risk of stroke and transient ischemic events, and both atypical and conventional antipsychotics have been associated with an increased risk of death.…”
mentioning
confidence: 99%
“…A recent report indicates that there is still considerable use of FGAs among older people. Based on data for 2.5 million Medicare beneficiaries in nursing homes during 2001, Briesacher et al (2005 reported that an estimated 27.6% of all Medicare beneficiaries were prescribed an antipsychotic drug at least once; about one quarter of them (7.3% of all Medicare beneficiaries) received an FGA.…”
Section: Discussionmentioning
confidence: 99%